Childhood trauma and dissociative symptoms predict frontal EEG asymmetry in borderline personality disorder. Issue 1 (1st January 2019) - Popkirov, Stoyan; Flasbeck, Vera; Schlegel, Uwe; Juckel, Georg; Brüne, Martin
ABSTRACT: Frontal EEG asymmetry (FEA) has been studied as both state and trait parameter in emotion regulation and affective disorders. Its significance in borderline personality disorder (BPD) remains largely unknown. Twenty-six BPD patients and 26 healthy controls underwent EEG before and after mood induction using aversive images. A slight but significant shift from left- to right-sided asymmetry over prefrontal electrodes occurred across all subjects. In BPD baseline FEA over F7 and F8 correlated significantly with childhood trauma and functional neurological "conversion" symptoms as assessed by respective questionnaires. Regression analysis revealed a predictive role of both childhood trauma and dissociative neurological symptoms. FEA offers a relatively stable electrophysiological correlate of BPD psychopathology that responds only minimally to acute mood changes. Future studies should address whether this psychophysiological association is universal for trauma- and dissociation-related disorders, and whether it is responsive to psychotherapy.